Long-Run money demand using divisia aggregates - Çelik, Sadullah (İktisadi ve İdari Bilimler Dergisi, 2003)
Divisia aggregates is discussed, as well as describing the cointegration mod- ... accompanied with the difficulties in analyzing the long-run money demand.